Turkey as an Educational Bridge: A Management and International Relations Perspective on Cross-Border Learning - Jundullah Rifqi Prasmanto; Anang Ma’ruf; Muhammad Fathurrahman Assidiq; Muhammad Faiz Diyaulhaq (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This study explores Turkey’s emerging role as a pivotal educational bridge in the context of international higher education, analyzed through the combined lenses of management and international relations. Turkey’s strategic use of education as a form of soft power, alongside its institutional efforts to internationalize higher education, underpins its ambition to foster diplomatic ties and enhance geopolitical influence. By examining cross-border educational partnerships and the mobility of international students from strategically significant regions, this research highlights both opportunities and challenges in Turkey’s educational branding. Despite notable progress, contradictions related to political interference, academic freedom, and quality assurance complicate Turkey’s global reputation as an education hub. The study employs a library research methodology, analyzing secondary sources to provide an integrative perspective on how education management intersects with foreign policy objectives. Findings suggest that Turkey’s educational diplomacy serves as a vital tool for geopolitical leverage but requires addressing internal governance issues to sustain credibility and effectiveness in the global education landscape.